The Biology And Ecology Of Schistosoma Spindale In Relation To The Epidemiology Of Cercarial Dermatitis In Peninsula.R Malaysia - Muthusamy, Krishnasamy (1999)

(untitled)
Objektif kajian ini adalah menkaji pelbagai faktor yang menyumbangkan kepada epidemiologi dermatitis serkaria yang diakibatkan oleh Schistosoma spindale di semenanjung Malaysia, dengan tumpuan khas pada suatu tempat endemik di Labu, Negeri Sembi Ian. The objective of this study was to study various factors that contributed to the epidemiology of cercarial dermatitis caused by Schistosoma spindale in peninsular Malaysia, with particular focus on an endemic area in Labu, Negri Sembi Ian.